Estimation of Aperture and Stiffness of Fractures under High Water Pressure Using Hydrological Data and Slurry Consolidating Body - Jianbo Li; Yanchun Xu (Geofluids)
The fractured limestone aquifers under coal seams bring great threat to coal production, and grouting engineering before mining is usually used to seal the fractures and prevent water inrushes. However, the grouting mechanism is still a difficult issue since the hidden fissures cannot be observed. In this paper, two characteristics of fractures filled with high-pressure water, deformation, and stiffness are studied to seek some good explanations for grouting. First, an ideal flow model composed of a borehole and a fracture is established with the fracture aperture as the main variable. The estimation methods for the aperture of fractures with high-pressure water before grouting and the stiffness of the fracture filled with slurry consolidating body during high-pressure grouting are proposed, and the millimeter-scale solution of deformation is obtained by using hydrological data and slurry consolidating body. Then, the methods are used for the field grouting practice, and its applicable conditions are given. The estimated apertures of the fractures with high-pressure water range from 2.08 to 2.56 mm. Under the grouting pressure of 15 MPa and the designed slurry diffusion radius of 30 m, the normal stiffness of the fracture filled with slurry consolidating body ranges from 0.5 to 14.4 GPa/m. The results meet the positive relationship between normal stiffness and fracture aperture got by the literature data and can be used for the study of grouting effect of the hidden fractures, including the evaluation of strength and water resistance of the slurry consolidating body. Our method of estimating the aperture and stiffness of fractures is applicable when grouting is used in the fractured limestone aquifers with high water pressure under coal seams before mining.